Interventions for reducing unplanned paediatric admissions: an observational study in one hospital. Issue 1 (28th March 2018) - Husk, Kerryn; Berry, Vashti; Tozer, Richard; Skipwith, Gina; Radmore, Robert; Ball, Susan; Ukoumunne, Obioha C; Logan, Stuart
Abstract : Objective: Evidence on how best to intervene to improve paediatric acute care and therefore reduce unplanned hospital admissions is weak. We describe service evaluation work at one hospital to assess interventions at critical clinical and service decision points. Design: We conducted an observational study using routine daily-collected data (April 2009–December 2015) from a medium-sized district general hospital in south-west UK, using before-and-after comparisons of admissions-related data to evaluate two interventions implemented in April and November 2014, respectively: (1) an advice and guidance (A&G) phone line, where a senior paediatrician is available for general practitioners (GPs) and emergency department (ED) and (2) a Short Stay Paediatric Assessment Unit (SSPAU). We analysed data on all admitted children (<18 years) in the catchment area (population estimate 27 740 in 2015). Outcomes were GP-referred attendances, ward admissions, less than 1 day admissions and length of stay. Results: A&G phone line was associated with a reduction in the mean number of less than 1 day admissions per month (difference in means before and after intervention −16.6 (95% CI −0.2 to −32.9)) and an increase in overall monthly bed-days (difference 72.5 (95% CI 21.0 to 124.0)), but there was little evidence of a change in GP-referred attendances or ward admissions. SSPAU was associated with a reduction in the mean number of monthly ward admissions (difference −34.6 (95% CI –21.3 to −48.0)) and less than 1 day admissions (difference in means −21.7 (95% CI −8.4 to −35.1)) and a reduction in the mean number of overall bed-days per month (difference −50.2 (95% CI −12.1 to −88.3)). Conclusions: Interventions for reducing time taken to senior clinician review may be effective in better managing paediatric acute care. Further work should explore results by age, condition and injury/illness status.